2015
DOI: 10.1111/josh.12307
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From the Whole Child and Coordinated School Health Approaches

Abstract: BACKGROUND The new Whole School, Whole Community, Whole Child (WSCC) model, designed to depict links between health and learning, is founded on concepts of coordinated school health (CSH) and a whole child approach to education. METHODS The existing literature, including scientific articles and key publications from national agencies and organizations, was reviewed and synthesized to describe (1) the historical context for CSH and a whole child approach, and (2) lessons learned from the implementation and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 22 publications
(43 reference statements)
3
70
0
3
Order By: Relevance
“…9,19,20 Conversely, without supplementary funds, school staff have previously reported not being able to engage in CSH initiatives because they were not compensated for their time. 20,21,38,39 We found that the availability of funds from government grants, external fundraising and/or student payment made it possible for some schools to offer regular free or subsidized breakfast, lunch or snack programs. In some cases though, those who wished to have student nutrition programs were limited by a lack of funds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9,19,20 Conversely, without supplementary funds, school staff have previously reported not being able to engage in CSH initiatives because they were not compensated for their time. 20,21,38,39 We found that the availability of funds from government grants, external fundraising and/or student payment made it possible for some schools to offer regular free or subsidized breakfast, lunch or snack programs. In some cases though, those who wished to have student nutrition programs were limited by a lack of funds.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,[21][22][23] When stakeholders, be they teachers, school staff, food service providers, families, community partners, health promotion officials or students, are engaged in the decisionmaking process, there is an increased sense of buy-in and ownership that leads to a personal commitment to sustain CSH initiative outcomes. 19,22,23,37,38 In our study, school staff members said they were not often consulted on discussions related to healthy eating in their schools, and one may assume this disengagement may have contributed to a lack of extracurricular supports for healthy eating within the social environment pillar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Les personnes qui ont vraiment à coeur d'améliorer les com portements sains des élèves, appelées « champions de la santé », jouent le rôle d'intermédiaires clés qui favorisent en con tinu les initiatives de santé en milieu sco laire au sein de la salle de classe et en dehors de celleci 20,21,35,36 . Dans le cadre de notre étude, les champions de la santé en milieu scolaire étaient les enseignants, qui consacraient du temps en dehors de la salle de classe (pause dîner, après l'école) à mettre en oeuvre des programmes et à superviser les élèves au sein de conseils d'action en matière de nutrition, de clubs d'écologie ou de concours extrascolaires portant sur les compétences alimentaires.…”
Section: Analyseunclassified